A population-based analysis of the risk of drug interaction between clarithromycin and statins for hospitalisation or death. Issue 1 (December 2015) - Mesgarpour, Bita; Gouya, Ghazaleh; Herkner, Harald; Reichardt, Berthold; Wolzt, Michael
Abstract Background Clarithromycin, known as a potent inhibitor of the cytochrome P450 isoenzyme CYP3A, may increase the plasma concentration of statins metabolized by this pathway; therefore, increase the risk of interaction with statins in reference to pharmacokinetic studies. This study aimed to characterize whether the concomitant use of a statin with clarithromycin is associated with serious outcomes among adult persons. Methods Health claims data of adult persons in the Regional Sickness Fund of Burgenland, Austria, who filled a prescription for clarithromycin between July 1, 2009 and June 30, 2012 were reviewed retrospectively. We assumed that the risk of hospitalisation increases acutely with the indication for taking an antibiotic, whereas statin use can be considered a chronic exposure with a low constant effect on hospitalisation. When defining the population as persons taking clarithromycin and the use of statins as the exposure we could achieve a comparable effect in both groups from the acute condition on hospitalisation. Therefore, we defined exposed patients as those who had overlapping treatment with a statin and unexposed controls as those who had filled a prescription for clarithromycin without concomitant statin therapy. Outcome was defined as a composite of hospital admission or death within 30 days after starting clarithromycin. We used generalised linear regression to model an association between outcome and exposure to statins. Results Among 28, 484 prescriptions of clarithromycin, 2317 persons were co-exposed to statins. Co-administration of CYP3A4 metabolized statins and clarithromycin was associated with a 2.11 fold increased risk of death or hospitalisation (95 % confidence interval [CI]: 1.79–2.48). This effect was explained by age, evidence of cardiovascular disease, diabetes mellitus and utilization of other antibiotics (multivariable adjusted risk ratio: 1.02, 95 % CI: 0.85–1.22). The sensitivity analyses did not change the significance of effect. Conclusions The risk for hospitalisation or death in persons receiving clarithromycin increases with age and cardiovascular disease but is not causally associated with statin-clarithromycine co-administration.